Implementasi LKPD Berbasis Higher Order Thinking Skills (HOTS) dengan Pictorial Riddle untuk Hasil Belajar Biologi - Azizah, Alfiana Nur; Utami, Sri; Kiswardianta, R. Bekti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This study aims to examine the application of LKPD (Learner Worksheets) focusing on Higher Order Thinking Skills (HOTS) using Pictorial Riddle (image-based riddles) to increase interest and learning outcomes in biology class VII at MTs An-Najihah, Kerjo Mojorejo Village, Kebonsari District, Madiun Regency on Animal and Plant Tissue Sub-Material. This research uses Classroom Action Research (PTK). There are 4 data collection techniques in this study, namely interviews, observations, tests and documentation. The use of HOTS-based LKPD with Pictorial Riddle is able to improve learning outcomes and student interest in the sub-material of Animal and Plant Tissues in class VII MTs An-Najihah. The completeness of students has increased in each cycle. In the pre-cycle of individual completeness amounted to 11 students and 32% classical completeness, in cycle I individual completeness amounted to 15 students and classical completeness to 43%. Then in cycle II individual completeness increased to 32 students and classical completeness to 91%. The conclusion of the research is that the implementation of HOTS-based LKPD with Pictorial Riddle can increase the interest and learning outcomes of VII grade students of MTs An-Najihah on the subject matter of Animal and Plant Tissues.